A study into the legal aspects of homeschooling in Malaysia / Dintas Gimfil Pikil @ Joyce, Mohd Azinuddin Abd Karim and Nik Saiful Amir Kamis - Pikil @ Joyce, Dintas Gimfil; Abd Karim, Mohd Azinuddin; Kamis, Nik Saiful Amir (2008)
A Study into the Legal Aspects of Homeschooling in Malaysia is a research paper focusing on the rights of homeschoolers in Malaysia. Homeschooling is a topic which touches on the rights of the parents to educate their children, the function of the state in education and the delicate balance between both in carrying out their roles. More importantly, the research paper will lay out the legal options, rights and liabilities of the homeschooler in Malaysia. The research is set out systematically, firstly dealing with the right of parents to educate their children, based on principles found in natural law and fundamental rights in Chapter Two. Secondly, Chapter Three deals with the role of the state in education, and what legitimate interests it may have in regulating education, which will by default affect homeschoolers. Thirdly, Chapter Four discusses the constitutional, statutory and regulatory provisions that affect homeschoolers in Malaysia, as well as the rights, liabilities and legal options for those who wish to practice homeschooling. Fourthly, Chapter Five lays out guidelines found in the laws and policies of other countries which practice homeschooling. This may be applicable to Malaysia for the purposes of any future attempts at legislating on homeschooling. Finally, Chapter Six sets out the conclusions and recommendation for homeschoolers in Malaysia.